2013
DOI: 10.3109/02713683.2013.774023
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Anti-oxidative Defence in Patients with Age-related Macular Degeneration

Abstract: The results of the present study show that there is a significant increase in oxidative stress in AMD patients and significant decrease in antioxidant defence, in the total thiol level and in PON1 activity in AMD patients compared with controls. The increased oxidative stress and decreased antioxidant levels may have a synergistic role in AMD development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…22 Previous studies indicated that total thiol levels were lower in patients with AMD compared to healthy subjects. 23,24 Similar to these studies, total thiol levels were lower in AMD patients in our study group compared to healthy subjects. However, in a recent study, Erel and Neselioglu 15 described that total thiol levels might remain in a plateau level despite the significant variability in plasma oxidant concentrations in the human metabolism.…”
Section: Discussionsupporting
confidence: 90%
“…22 Previous studies indicated that total thiol levels were lower in patients with AMD compared to healthy subjects. 23,24 Similar to these studies, total thiol levels were lower in AMD patients in our study group compared to healthy subjects. However, in a recent study, Erel and Neselioglu 15 described that total thiol levels might remain in a plateau level despite the significant variability in plasma oxidant concentrations in the human metabolism.…”
Section: Discussionsupporting
confidence: 90%
“…), TTS (total thiol status), PON1 (paraoxonase) and high‐level TOS (total oxidant status) (Uğurlu et al. ) and concentration of plasma malondialdehyde (MDA; Evereklioglu et al. ) were indicated.…”
Section: Discussionmentioning
confidence: 99%
“…[2],[3] Serologic biomarkers of AMD incidence and progression have been sought, primarily relating to pathways responsive to inflammation,[57] cell stress (particularly oxidative stress) or toxicity. [2],[7],[8] Such studies have, however, provided inconsistent results and, hence, clinical practice still solely relies on the evaluation of phenotypic characteristics, such as fundus appearance. Biofluid markers may be useful to help predict incidence and prevalence of the disease, but reliable markers are still lacking.…”
Section: Introductionmentioning
confidence: 99%